Novel Approach for Improving Papaya Fruit Storage with Carnauba Wax Nanoemulsion in Combination with Syzigium aromaticum and Mentha spicata Essential Oils - Oliveira Filho, Josemar Gonçalves de [UNESP]; Duarte, Larissa G. R.; Silva, Yasmin B. B.; Milan, Eduardo P.; Santos, Higor V.; Moura, Thaís C.; Bandini, Vitor P.; Vitolano, Luís Eduardo S.; Nobre, Jacqueline J. C.; Moreira, Cristiane T.; Mitsuyuki, Milene C.; Bogusz Junior, Stanislau; et al. (My University, 2023)
Application of hydrophobic coatings, such as carnauba wax nanoemulsions, combined with natural antimicrobials, has been demonstrated to be an effective solution in extending the shelf life of fruits. The present study evaluated the effectiveness of carnauba wax nanoemulsion (CWN) coatings containing free or encapsulated with β-cyclodextrin (β-CD) essential oils of Syzigium aromaticum (CEO) and Mentha spicata (MEO) for the post-harvest conservation of papaya fruit. The chemical composition of the essential oils (EOs) was analyzed using GC-MS. Subsequently, coatings incorporating free and encapsulated EOs were prepared and applied to papaya fruit. Fruit was evaluated for post-harvest quality parameters during 15 days of storage. Clove essential oil presented as main compounds eugenol (89.73%), spearmint and carvone (68.88%), and limonene (20.34%). The observed reduction in weight loss in coated fruit can be attributed to the formation of a physical barrier provided by the coating. Compared to the control group, which experienced the highest weight loss of 24.85%, fruit coated with CWN and CWN-MEO:β-CD exhibited significantly lower weight loss percentages of only 5.78% and 7.5%, respectively. Compared to the control group, which exhibited a release of ethylene at a rate of 1.3 µg kg−1 h−1, fruit coated with CWN, CWN-MEO:β-CD, and CWN-MEO coatings demonstrated a lower ethylene release rate at 0.7 µg kg−1 h−1. Although the physical-chemical properties of papayas, including pH, Brix, titratable acidity, color, and texture, remained largely unchanged during storage with the coatings, analysis of incidence and severity of papaya post-harvest deterioration revealed that coatings containing essential oils effectively acted as antifungals in the fruit. Microscopy images showed that CWN and CWN-MEO:β-CD coatings are more uniform compared to the others. The edible coatings, especially CWN and CWN-MEO: β-CD, can act as antimicrobial coatings on papaya fruit, increasing their conservation during post-harvest storage.
Keywords: hydrophobic coatings; natural antifungal compounds; post-harvest; preservative